Pengembangan Media Pembelajaran Berbasis Tes Soal dengan Tema Essen Und Trinken pada Media Easy Test Maker - Muhammad Ikhsan Ramadhan; Surya Masniari Hutagalung (CV. Alim's Publishing, 2026)
This study aims to describe the process of developing test-based learning media on the topic of Essen und Trinken (Food and Drink) using the Easy Test Maker application, and to measure the outcomes of this development in A1-level German language learning. This research and development (R&D) study employed the Richey and Klein model, consisting of three stages: planning, production, and evaluation. The subjects were eleventh-grade students at MAN 2 Model Medan. The data source consisted of vocabulary and sentence-structure material on the topic of Essen und Trinken, adapted from the textbook Netzwerk neu A1: Deutsch als Fremdsprache. Data were collected through classroom observation, interviews with German teachers, pre-tests and post-tests, and expert validation of the material. The findings show that the development of Easy Test Maker-based media was successfully carried out through the three stages. In the evaluation stage, students' learning outcomes improved from the pre-test to the post-test on both multiple-choice and essay items. Qualitatively, students showed increased motivation, confidence, and engagement after using the media. It can be concluded that test-based learning media developed with Easy Test Maker is effective as an interactive evaluation alternative in German language learning, particularly on the topic of Essen und Trinken.